Preoperative anaemia management in patients undergoing vascular surgery. Issue 12 (30th September 2020) - Nandhra, S.; Chau, M.; Klein, A. A.; Yeates, J. A.; Collier, T.; Evans, C.; Agarwal, S.; Richards, T.; ,
Abstract : CAVIAR is a multicentre prospective stepped observational study encompassing 160 patients undergoing vascular intervention. The aim was to identify whether it was feasible to establish a preoperative anaemia pathway and, if so, the efficacy of intravenous iron for treatment of preoperative anaemia. Large barriers prevented implementation of an intravenous iron pathway, with only ten patients receiving intravenous iron and a small increase in haemoglobin level (mean 5·7 (95 per cent c.i. 4·5 to 6·9) g/l). Preoperative anaemia was associated with a longer hospital stay and greater transfusion requirement. Anaemia common and dedicated pathway difficult to instigate